2012
DOI: 10.1007/s12291-012-0247-2
|View full text |Cite
|
Sign up to set email alerts
|

Total Serum Immunoglobulin E in Children with Asthma

Abstract: Immunoglobulin (Ig) E has been shown to be a major contributing factor for the development of bronchial hyperresponsiveness in asthma. An elevation in serum IgE levels contributes to asthma and is considered a potent predictor of the development of asthma. The objectives of the present study were to estimate the levels of total serum IgE in asthmatic and healthy control subjects and to investigate the relationship of various demographic and clinical characteristics with the total serum IgE level in asthmatics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 12 publications
2
19
0
4
Order By: Relevance
“…18 Various other studies have showed Serum IgE levels were high in asthmatics as compared to normal subjects. 5,19 In the present study, the mean values of serum IgE levels in mild, moderate and severe asthmatic children was 625.25 IU/mL, 871.77 IU/mL, 1225.05 IU/mL respectively (Table 3) and were found to be statistically significant when the levels were compared between these three groups (p < 0.001). Present study was comparable to a longitudinal study done in Melbourne, Australia, of asthmatic children, which studied mean serum IgE level at 7, 10 and 14 years of age by grade of disease severity and results showed higher IgE levels in patients with more severe and persistent asthma compared with those with mild, episodic asthma.…”
Section: Discussionsupporting
confidence: 47%
“…18 Various other studies have showed Serum IgE levels were high in asthmatics as compared to normal subjects. 5,19 In the present study, the mean values of serum IgE levels in mild, moderate and severe asthmatic children was 625.25 IU/mL, 871.77 IU/mL, 1225.05 IU/mL respectively (Table 3) and were found to be statistically significant when the levels were compared between these three groups (p < 0.001). Present study was comparable to a longitudinal study done in Melbourne, Australia, of asthmatic children, which studied mean serum IgE level at 7, 10 and 14 years of age by grade of disease severity and results showed higher IgE levels in patients with more severe and persistent asthma compared with those with mild, episodic asthma.…”
Section: Discussionsupporting
confidence: 47%
“…Elevated serum total IgE in asthma has been associated with poor pulmonary function, increased airway inflammation, and eosinophilia . Further, pediatric patients with asthma demonstrate increased total IgE, and total IgE has been shown in some studies to correlate with airway inflammation . Still, patterns of lower airway inflammation in children with severe‐persistent asthma remain poorly characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Выявлена обратная корреляционная связь между тяжестью бронхиальной астмы и количе-ством лимфоцитов периферической крови [2,17,18]. Изменения в гуморальном звене иммунитета обусловлены приоритетным синтезом IgE и уве-личением концентрации тех иммуноглобулинов, которые реализуют реакцию гиперчувствитель-ности немедленного типа [19,20]. Закономерно, что при отсутствии контроля над течением ато-пической бронхиальной астмы, вследствие пер-систенции воспаления, наблюдается гиперпро-дукция IgЕ.…”
Section: Discussionunclassified
“…Наибольшее значение в детском возрасте име-ет атопический (IgE-опосредованный) тип реа-гирования [5,20]. Возможно, отсутствие адекват-ного контроля атопической бронхиальной астмы обусловлено особенностями эндогенной регуля-…”
Section: Introductionunclassified